Efektivitas Model Pembelajaran CRH-LCC Terhadap Peningkatan Hasil Belajar pada Materi Energi Kelas X ULP SMKN 3 Bandung - Marlina, Rina; Chusni, Muhammad Minan; Karyadinata, Rahayu (CAHAYA: Journal of Research on Science Education, 2025)
This study aims to determine the effectiveness of the Course Review Horay (CRH) learning model in improving students' learning outcomes on the topic of Energy and its Changes. The background of this study is the low average formative test scores for this topic, despite the fact that the basic material has been taught at the elementary and middle school levels. As a result, the CRH learning model, coupled with the learning experience through the Quiz Competition (LCC), was tested to strengthen and review the material in an interactive and engaging way. The research method used is descriptive qualitative with a one-group pretest-posttest design, analyzed using SPSS version 27. The sample consists of 34 students from class 10 ULP 2 out of a total population of 120 students. Data were obtained from pretest and posttest results. Normality testing using the Shapiro-Wilk test resulted in significance values of 0.011 and 0.047 for pretest and posttest, respectively, indicating that the data were not normally distributed. Hypothesis testing was carried out using the nonparametric Wilcoxon test, with a significance value of 0.01, which is less than 0.05, leading to the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (H1). The results indicate that the CRH learning model has a significant effect on improving students' learning outcomes. The effectiveness of the learning model is categorized as fairly effective, with an N-Gain value of 58.52%.